Analisis Karakteristik Tipe Fluida Mata Air Panas Di Hutan Pinus Lahendong Dengan Menggunakan Spektrofotometri - Jouhari Wote; Rolles Nixon Palilingan; Jeane Rende; Jeilen G. N. Nusa (Jurnal FisTa : Fisika dan Terapannya, 2023)
Pine Forest is one of the tourist attractions in Lahendong Village, which has geothermal manifestations in the form of hot springs, which shows that the area has geothermal potential. The purpose of this study was to determine the type of fluid manifested by hot springs in the Pine Forest using geochemical methods. The results of this study indicate that the temperature at the manifestation is 40°C while the degree of acidity of the pH of hot water has a value of 4 which indicates the acidity level of hot water is acidic. The type of fluid that exists in the manifestation area of hot water in the Pine Forest is the type of fluid sulphate water and sulfate water is a fluid that is formed at shallow depths and is formed as a result of the condensation process of geothermal gas towards near the surface. This is because the results of chemical analysis show that the element SO4 is the most dominant element and contains SO4 gas. Hot water that has a sulfate type is water that is formed at shallow depths and is formed as a result of the process of condensing geothermal gas towards near the surface. The geothermal gas with gas content (water and carbon) is basically dissolved in the fluid content which is located in the deep zone but separated from the chloride water. Sulphate water is usually at the boundary and not far from the main upflow zone.